Truth and Revolution in Marx's Critique of Society - Bohlender, Matthias. author. aut Link
XVI, 216 p. 1 illus.
Keywords: This book deals with a central aspect of Marx’s critique of society that is usually not examined further since it is taken as a matter of course: its scientific claim of being true. But what concept of truth underlies his way of reasoning which attempts to comprehend the social and political circumstances in terms of the possibility of their practical upheaval? In three studies focusing specifically on the development of Marx’s scientific critique of capitalist society, his journalistic commentaries on European politics, and his reflections on the organisation of revolutionary subjectivity, the authors carve out the immanent relation between the scientifically substantiated claim to truth and the revolutionary perspective in Marxʼs writings. They argue that Marx does not grasp the world ‘as it is’ but conceives it as an inverted state which cannot remain what it is but generates the means by which it can eventually be overcome. This is not something to be taken lightly: Such a concept has theoretical, political and even violent consequences – consequences that nevertheless derive neither from a subjective error nor a contamination of an otherwise ‘pure’ science. By analyzing Marx’s concept of truth the authors also attempt to shed light on a pivotal problematique of any modern critique of society that raises a reasoned claim of being true. Matthias Bohlender is Professor of Political Theory at the School of Cultural Studies and Social Sciences, Universität Osnabrück, Germany. Anna-Sophie Schönfelder is Research Associate at the DFG Collaborative Research Centre “Dynamics of Security”, Justus-Liebig-Universität Gießen, Germany. Matthias Spekker is Associate Lecturer in Political Theory and the History of Ideas and currently teaching at the Leuphana Universität Lüneburg, Germany. The authors worked together in the DFG funded research project. “Marx and the ‘criticism in a hand-to-hand fight' – On a genealogy of modern critique of society”, Universität Osnabrück, Germany.